Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/2040-2392-4-14
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of transcriptional targets of RORA reveals direct regulation of multiple genes associated with autism spectrum disorder

Abstract: BackgroundWe have recently identified the nuclear hormone receptor RORA (retinoic acid-related orphan receptor-alpha) as a novel candidate gene for autism spectrum disorder (ASD). Our independent cohort studies have consistently demonstrated the reduction of RORA transcript and/or protein levels in blood-derived lymphoblasts as well as in the postmortem prefrontal cortex and cerebellum of individuals with ASD. Moreover, we have also shown that RORA has the potential to be under negative and positive regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 99 publications
2
112
0
2
Order By: Relevance
“…24 RORa polymorphisms have further been implicated in posttraumatic stress disorder 22 and autism spectrum disorder. 45,46 We found rs809736 to be nominally associated with RORa expression in the present sample with the same direction of effect, that is, the allele associated with response in STAR*D was associated with lower RORa expression in the present study. Nevertheless, rs809736 was not replicated in the large PGC pharmacogenetic sample, hence, the nominal significant association of rs809736 with RORa gene expression in our cohort needs further replication.…”
supporting
confidence: 65%
“…24 RORa polymorphisms have further been implicated in posttraumatic stress disorder 22 and autism spectrum disorder. 45,46 We found rs809736 to be nominally associated with RORa expression in the present sample with the same direction of effect, that is, the allele associated with response in STAR*D was associated with lower RORa expression in the present study. Nevertheless, rs809736 was not replicated in the large PGC pharmacogenetic sample, hence, the nominal significant association of rs809736 with RORa gene expression in our cohort needs further replication.…”
supporting
confidence: 65%
“…This makes RORA an important gene/gene product in the etiology/pathology of AD. Indeed recent ChIP-on-chip studies have indicated an over-representation of genes linked with learning, memory and cognition among probable regulatory targets of RORA [57]. Thus, on the basis of the data presented here, we here posit an important link between hippocampal RORA and AD.…”
Section: Jactive Module Componentsmentioning
confidence: 57%
“…Figure 8 presents a working model that integrates the results of these studies with those of our earlier studies that demonstrated the opposite regulation of RORA by male and female hormones and the regulation of CYP19A1 by RORA [16,38]. In this model, a reduction in RORA expression, which may be induced by increased methylation, which we have demonstrated previously in cell lines from individuals with ASD [12] is expected to lead to a decrease in CYP19A1 (aromatase), which, in turn, would result in the accumulation of its substrate testosterone.…”
Section: Discussionmentioning
confidence: 93%